El principio iura novit curia en la acción de protección - Guamán Aguirre, Glenda Gildalid (Machala, Utmachala, 2022)
There is an excessive use of the Iura Novit Curia principle by judges when resolving protection actions to the detriment of the principle of effective judicial protection, due process and legal certainty. This article has the objective of analyzing the application of the iura novit curia principle by constitutional judges when issuing sentences within the jurisdictional action of protection action; for which a descriptive research based on historical-logical, exegetical and analytical-synthetic methods was developed, as well as the content analysis technique. Among the results, it is meant that, given the existence of legal problems in the application of this principle, in terms of limits, scope, role of the judge and impartiality of the administrators of justice, it is suggested to the National Council of the Judiciary the creation of an instruction oriented to constitutional judges, with the purpose of guaranteeing, in addition to their instruction, due respect for the constitutional rights of citizens, which cannot be violated by subjectivity or excess of the procedural principle iura novit curia.
Existe un excesivo uso del principio Iura Novit Curia por parte de los juzgadores al resolver las acciones de protección en desmedro del principio de tutela judicial efectiva, debido proceso y seguridad jurídica. Este artículo tiene el objetivo de analizar la aplicación del principio iura novit curia por los jueces constitucionales al dictar sentencia dentro de la acción jurisdiccional de acción de protección; para lo cual se desarrolló una investigación descriptiva sustentada en los métodos histórico-lógico, exegético y analíticosintético, así como la técnica de análisis de contenido. Entre los resultados se significa que, ante la existencia de problemas jurídicos en la aplicación de este principio, en cuanto a límites, alcances, rol del juzgador e imparcialidad de los administradores de justicia se sugiere al Consejo Nacional de la Judicatura la creación de un instructivo orientado a los jueces constitucionales, con el propósito de garantizar, además de la instrucción de estos, el debido respeto a los derechos constitucionales de los ciudadanos, los cuáles no pueden ser violados por la subjetividad o extralimitación del principio procesal iura novit curia.
Keywords: IURA NOVIT CURIA; ACCION ORDINARIA DE PROTECCION; DERECHO CONSTITUCIONAL